Integration of Universal Design for Learning in Creative Arts Education: Perspectives From Basic Schools in Suame Municipality, Ashanti Region, Ghana - Okyere, Akua Anima; Adom, Dickson; Kquofi, Steve; Sampene, Akua Asantewaa Badu; Buami, Edem Kwami (Studies in Learning and Teaching, 2024)
The existing teaching approaches used for teaching Creative Arts in basic schools in Ghana do not adequately address the diverse needs of students. This study aimed to investigate the integration of Universal Design for Learning (UDL) in Creative Arts education as an intervention to achieve high inclusivity and heighten the academic success of students in selected private and public basic schools in the Suame municipality of Ghana. The study was conducted using a sequential exploratory mixed methods design with phenomenology and descriptive survey as the main research methods. Data collection tools such as personal and FGD interviews, lesson observations, surveys, and academic performance evaluations aided in uncovering the nuanced insight of stakeholders in shedding light on the intricate dynamics of UDL adoption within the context of Creative Arts education in Ghana. The results showed that integration of UDL practices in Creative Arts education enhances inclusivity, engagement, and academic achievement among students with diverse learning needs. The study’s novelty is evident in the deployment of the UDL principles in teaching and learning activities of Creative Arts that successfully catered to the individualized needs of students, promoted active participation, and created a more equitable and effective learning environment.